2005
DOI: 10.1017/s0272263105050163
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Focus on Form and Second Language Learning

Abstract: Incidental focus on form overtly draws learners' attention to linguistic items as they arise spontaneously—without prior planning—in meaning-focused interaction. This study examined the effectiveness of incidental focus on form in promoting second language (L2) learning. Seventeen hours of naturally occurring, meaning-focused L2 lessons were observed in 12 different classes of young adults in a private language school in Auckland, New Zealand. A total of 491 focus-on-form episodes (FFEs) were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
290
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(311 citation statements)
references
References 30 publications
18
290
3
Order By: Relevance
“…He found that when learners produced more complex or accurate forms in modified output, they were more likely to produce these forms in subsequent utterances, again suggesting sustained impact. Loewen (2005) in similar vein observed that successful uptake in focus-on-form episodes served as a significant predictor of correct test scores, further evidence to support the assumption that uptake reflects or indeed promotes language development.…”
Section: Impact Of Uptake On Language Learningsupporting
confidence: 63%
See 2 more Smart Citations
“…He found that when learners produced more complex or accurate forms in modified output, they were more likely to produce these forms in subsequent utterances, again suggesting sustained impact. Loewen (2005) in similar vein observed that successful uptake in focus-on-form episodes served as a significant predictor of correct test scores, further evidence to support the assumption that uptake reflects or indeed promotes language development.…”
Section: Impact Of Uptake On Language Learningsupporting
confidence: 63%
“…Table 1 below summarises key findings from the research reviewed above on focus on form. Lightbown and Spada (1990), Doughty and Varela (1998), Harley (1998), Muranoi (2000), Ellis (2002), Mennim (2003), Lyster (2004), Loewen (2005), Bouffard and Sarkar (2008) Use of focuson-form instruction in CLT classrooms Focus on form may occur without interfering with the communicative flow of the lessons Seedhouse (1997), Doughty and Varela (1998), Ellis et al (2001aEllis et al ( 2001b Effectiveness of focus-onform instruction depending on type Using both explicit and implicit focus-on-form strategies can promote language learning Spada (1997) Using implicit eliciting focus on form can promote language learning Lyster (2004) and Loewen (2004) Using explicit focus-on-form strategies can promote language learning Ellis (2002) and Fuente (2006) Research on learners Learners believe that they can attend to form and meaning at the same time Doughty and Varela (1998) Learner-driven independent focus on form (learner noticing) seems to have positive impact on their L2 proficiency Mackey (2006), Mennim, (2007, Hanaoka (2007) When learners initiate focus on form they seem to address lexical aspects in particular Williams (1999), Ellis et al (2001a) More proficient learners are likely to pay more attention to form than less proficient learners Williams (1999) Research on teachers Discrepancies in teacher beliefs and practice in relation to their use of focus on form in communicatively oriented classrooms Basturkmen et al (2004) TeachersÕ experience seems to play a role in teachersÕ use of focus on form Mackey, et al (2004) Corrective feedback Iwashita (2003: 2) defines corrective feedback as Ôsome kind of native speaker response to what the learner has saidÕ; it may in fact be better understood as some kind of response from a more expert language user, often a teac...…”
Section: Focus-on-form Instruction: Research On Learnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some types of corrective feedback such as metalinguistc feedback and clarification requests usually demand modification or self-repair on the part of learners, while other types of corrective feedback such as recasts demands no self-repair or modified output. While using learners responses to corrective feedback as a yardstick for measuring the effectiveness of feedback has invoked some criticism (e.g., Long, 2007), some researchers suggested a link between certain types of learners' output in response to corrective feedback and subsequent L2 development (e.g., Loewen, 2005;McDonough, 2004McDonough, , 2005McDonough & Mackey, 2006). The aim of the current study is to investigate the association between learners' responses to recasts and subsequent development.…”
Section: Studentmentioning
confidence: 96%
“…While students expect it (Nunan, 1998), and not providing it can contribute to deficient interlanguages (Lightbown & Spada, 1999), error identification is a poor means of grammar feedback, as grammar learning interacts with rhetorical competency and culture performance (Fazio, 2001). Grammar feedback may be more effective if it is incidental, or accompanies attention to semantics (Loewen, 2005). The prevailing wisdom is that grammar feedback should reflect previously-announced, limited and focused criteria (Truscott, 2001).…”
Section: Introductionmentioning
confidence: 99%